Does the Indonesian Automotive Industry Have What it Takes to Compete in Post 2015 AFTA? - Muyanja Ssenyonga (Journal of World Trade Studies, 2012)
This research examines the state of competitiveness of the Indonesian automotive Industry today; identify opportunities and challenges, facing the Indonesian automobile industry; address efforts made to develop the opportunities and address the challenges; and draw policy recommendations that are potent to address problems, obstacles, and challenges facing the automotive industry. The study primarily uses a qualitative research approach, and employs research methods including semi structured interviews, in depth interviews, literature review of government policies, reports, and statistics on automotive product production, sales volumes, contribution to the economy, exports and imports; research reports from the Agency for the Development and Application of Technology (BPPT); reports and statistics issued by the Association of Indonesia Automitive Industries (GAIKINDO), and the European Chamber of Commerce (Automotive Division). Findings show that Indonesian automotive industry and market posted strong growth of 10 percent during the 2007-2011 period. This is reflected in production and sales figures that have showed an upward trend in line with the general performance of the economy. The Indonesian automotive industry in some respects is ready for post 2015 ASEAN. This is discernible from a number of areas such as semi-skilled and skilled labor; a supportive regulatory framework that protects domestic automotive product manufacturers from unfair competition from ASEAN and non ASEAN manufacturers; improvement in government governance as reflected in rising transparency, some major inroads in corruption control, improvement in macroeconomic management which has created a low inflation, stable exchange rate, low national debt to GDP ratio, capital inflows, and the tax regime.